The impact of pathogen reduction on ABO isoagglutinin titers in apheresis platelets - Mikayel Yeghiazaryan; Yembur Ahmad; Jessie Singer; Vaanush Nazaryan; Craig Fletcher; Yamac Akgun (Hematology, Transfusion and Cell Therapy)
Background: Platelet transfusions are a cornerstone of modern medical care, used across various clinical contexts. Ensuring the compatibility of blood products, especially regarding ABO isoagglutinins, is critical to minimize adverse reactions. Pathogen reduction technologies have been widely adopted to enhance the safety of blood products, however, the impact of such treatments on ABO isoagglutinin titers in platelet products remains unclear. Methods: This study analyzed 60 apheresis platelet donations, including type O, A, and B donors, using the INTERCEPT® Blood System for pathogen reduction. Samples were collected both from donor whole blood at the time of apheresis (Retention) and from the final pathogen-reduced platelet product after it had passed through the compound adsorption device (Post-CAD). ABO isoagglutinin titers, including both IgM and IgG classes, were measured using solid-phase technology on the NEO Iris platform. Results: This study found a significant reduction in IgM isoagglutinin titers in Post-CAD samples, with 99 % of Retention titers being greater than or equal to their Post-CAD counterparts. IgG titers exhibited more variability, with 9 % of Post-CAD samples displaying higher titers than Retention samples. Statistical analysis confirmed differences between Retention and Post-CAD samples for both IgM and IgG titers, with p-values <0.05 in most comparisons. Conclusion: Pathogen reduction using the INTERCEPT® Blood System effectively reduces ABO isoagglutinin titers in apheresis platelets, potentially lowering the risk of hemolytic transfusion reactions. This reduction is beneficial for safer out-of-group platelet transfusions, especially in vulnerable populations such as pediatric patients. These findings support the continued use of pathogen-reduced platelets in transfusion medicine to enhance both safety and availability of blood products.